2022
DOI: 10.1038/s41419-021-04491-0
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-124-3p.1 sensitizes hepatocellular carcinoma cells to sorafenib by regulating FOXO3a by targeting AKT2 and SIRT1

Abstract: As a multikinase inhibitor, sorafenib is commonly used to treat patients with advanced hepatocellular carcinoma (HCC), however, acquired resistance to sorafenib is a major obstacle to the effectiveness of this treatment. Thus, in this study, we investigated the mechanisms underlying sorafenib resistance as well as approaches devised to increase the sensitivity of HCC to sorafenib. We demonstrated that miR-124-3p.1 downregulation is associated with early recurrence in HCC patients who underwent curative surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…However, Sorafenib has also been associated with widespread resistance and side effects in clinical practice [35][36] . Available evidence suggests that miRNAs are involved in multiple aspects of tumor cell differentiation, proliferation, regulation, invasion, metastasis, autophagy, and tumor microenvironment [37][38][39] , and can reverse Sorafenib resistance in HCC treatment [40][41][42] and enhance the clinical e cacy of Sorafenib. Although hepatocellular carcinoma treatment has come to the era of immunotherapy in recent years, especially since the FDA has approved the combination of atelelizumab and bevacizumab for improving overall survival in patients with advanced HCC [43][44] , Sorafenib is still considered as the rst-line agent for systemic treatment of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sorafenib has also been associated with widespread resistance and side effects in clinical practice [35][36] . Available evidence suggests that miRNAs are involved in multiple aspects of tumor cell differentiation, proliferation, regulation, invasion, metastasis, autophagy, and tumor microenvironment [37][38][39] , and can reverse Sorafenib resistance in HCC treatment [40][41][42] and enhance the clinical e cacy of Sorafenib. Although hepatocellular carcinoma treatment has come to the era of immunotherapy in recent years, especially since the FDA has approved the combination of atelelizumab and bevacizumab for improving overall survival in patients with advanced HCC [43][44] , Sorafenib is still considered as the rst-line agent for systemic treatment of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modifications of FOXO3a can regulate its transcriptional activity and nuclear location, enabling it as a potential target for novel strategy in cancer treatment. 42,43 Some studies reported that high expression of FOXO3a was associated with improved OS in patients with solid tumor. However, other studies indicated that the high expression of FOXO3a was related to poor OS in comparable patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were euthanized after 21 days of inoculation, and the s.c. tumor were dissected and analyzed. Sorafenib significantly inhibited HCC growth, [26] but the ABX treatment group significantly reduced its effect. However, after resupplementation with NaBu in the ABX treatment group, the tumor volume was significantly reduced post targeted therapy (Figure 5L, M).…”
Section: Butyrate Supplement Improves Tyrosine Kinase Inhibitor Thera...mentioning
confidence: 92%